2018
DOI: 10.3390/sym10090416
|View full text |Cite
|
Sign up to set email alerts
|

Intrasession Reliability of the Tests to Determine Lateral Asymmetry and Performance in Volleyball Players

Abstract: The development of lateral asymmetries in athletes could have an influence on performance or injuries. The aim of this study was to determine the within-day reliability of the symmetry tests and the performance tests, and explore the relationship between them. Eighteen male volleyball players (18.1 ± 2.1 years) participated in this study. Seven lateral symmetry assessments were used, namely: lateral symmetry through tensiomyography (LS), active knee extension (AKE), Y-balance test (YBT), muscular electrical ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…Lateral asymmetries were found in the Dm and in the Vrn of VL and VM, RF and BF of volleyball players 26. In addition, TMG has shown excellent reproducibility of lateral symmetry in these athletes 58. In professional cyclists it has been reported that there are no significant differences in VL, VM, RF and BF between the right side and left the side, in terms of Dm and Tc 16,17.…”
Section: Tmg Parameters As Symmetry Measurementioning
confidence: 95%
“…Lateral asymmetries were found in the Dm and in the Vrn of VL and VM, RF and BF of volleyball players 26. In addition, TMG has shown excellent reproducibility of lateral symmetry in these athletes 58. In professional cyclists it has been reported that there are no significant differences in VL, VM, RF and BF between the right side and left the side, in terms of Dm and Tc 16,17.…”
Section: Tmg Parameters As Symmetry Measurementioning
confidence: 95%
“…However, our findings are in line with the high interday reliability found in other jump tests, such as the CMJ (7) with a movement pattern similar to the volleyball attack take-off. In addition, the high intrareliability found in this test (20) seems to point out that it is a very useful jump test to control volleyball players' performance. This high interday and intraday reliability could possibly be due to the high number of repetitions that volleyball players perform this technical gesture.…”
Section: Discussionmentioning
confidence: 86%
“…However, lateral asymmetry results could depend on the reliability of the tests that have been used for its detection because not all tests have the same intraday reliability in well-trained volleyball players (20). In addition, it still seems necessary to determine the most appropriate method to calculate the asymmetry based on whether the best performance value is retained for the analysis or, on the contrary, the average value of the different attempts made as recommended by Bishop et al (3).…”
Section: Introductionmentioning
confidence: 99%
“…Up : (CV X , CV Y ) = (2, 3) and (m, n) = (500, 700); down : (CV X , CV Y ) = (3,5) and (m, n) = (700, 1000). Table 3 indicates that all p-values are more than 0.05 and consequently the Shapiro-Wilk's test verified the normality of the proposed test statistic.…”
Section: Third Columnmentioning
confidence: 99%
“…The division of the standard deviation to the mean of population, CV = σ µ , is called as coefficient of variation (CV) which is an applicable statistic to evaluate the relative variability. This free dimension parameter can be widely used as an index of reliability or variability in many applied sciences such as agriculture, biology, engineering, finance, medicine, and many others [1][2][3]. Since it is often necessary to relate the standard deviation to the level of the measurements, the CV is a widely used measure of dispersion.…”
Section: Introductionmentioning
confidence: 99%